Pangenome-scale annotation of mycobacteriophages for dissecting phage–host interactions based on a sequence clustering and structural homology analysis strategy - Xiao Guo; Zheng-Guo He (mSystems)
ABSTRACT With the increasing severity of bacterial drug resistance, there is a growing need for phages with well-defined genetic backgrounds to combat drug-resistant infections. Mycobacteriophages constitute the largest genome-sequenced phage group; however, the vast majority of these phage proteins have not yet been effectively annotated. In this study, we employed a structure-based similarity search approach to improve protein annotation. Through the application of this approach to 240,754 proteins from 2,169 mycobacteriophage genomes, we increased the protein annotation rate from 34% to 52.11%. Additionally, we identified a series of predicted counter-defense proteins, including anti-CRISPR proteins and antitoxins, and inferred the potential interaction network of phage-encoded proteins involved in replication, transcription, and translation with host-associated molecular machinery. This study addresses a substantial gap in the current knowledge of the potential function of phage proteins and provides key insights into the interactions between mycobacteriophages and their hosts.IMPORTANCEMycobacteriophages constitute the largest group of phages with sequenced genomes. However, a significant portion of these phage proteins have not yet been effectively annotated, seriously hindering our understanding of the basic biological processes of phage–host interactions and their practical applications. This study utilized a structure-based similarity search approach to enhance phage protein annotation. This approach led to the identification of novel predicted protein folds, structural domain fusion phenomena, and putative new enzymes. Additionally, the study identified a series of phage-encoded proteins that may play a role in hijacking host-associated replication, transcription, and translation processes, providing insights into the molecular mechanisms underlying mycobacteriophage interactions with host machinery. This study addresses a critical knowledge gap regarding the potential function of phage proteins and provides key insights into the interactions between mycobacteriophages and their hosts.